멀티미디어 온라인 학습 컨텐츠의 특성이 학습자의 학습 효과에 미치는 영향에 관한 연구 - 배순한; 김지훈; 임양환; Bae, Soon Han; Kim, Ji Hoon; Lim, Yang Whan ((사)디지털산업정보학회 논문지, 5(1), 2009)
Recently a rapid development of Information Technology including Internet have brought new way of education such as Distance education, Cyber University, Home Schooling and so on. This change of education have also brought about the change of a tool and medium for education. It is a using multimedia contents in education. Using the multimedia learning contents on line education is considered as one of new way of education and expected to bring learner's better performance. Therefore, it's necessary to research online education contents and its design. In this paper, we discussed how the multimedia contents should be designed to help to reinforce what the learner have learned and researched a critical factor of online contents to effect on learner's better performance.